Synthesis of Three-Dimensional Benzophenone Analogues Based on a [2.2]Paracyclophane Scaffold - Wu, Shiqi; Micouin, Laurent; Benedetti, Erica (Synlett, 2024)
Herein, we report the synthesis of functionalized three-dimensional benzophenone analogues derived from [2.2]paracyclophane (pCp). The potential use of these compounds as photocatalysts is disclosed. Benzophenone and its derivatives are well-known photoactive compounds that have been extensively employed over the years as catalysts to promote a variety of transformations activated by light. The development of differently substituted three-dimensional versions of such compounds may significantly expand the range of their applications in photocatalysis. Exploitation of the planar chirality of substituted paracyclophanes may also lead to significant innovations in different fields. [2.2]Paracyclophane-based benzophenone derivatives incorporating reactive ester or amide functions at their pseudo-gem position are successfully prepared in a selective manner. Examples of both racemic and enantiopure compounds are reported. As a proof of concept, the catalytic activities of the newly synthesized molecules are compared to that of benzophenone in a known photooxidation reaction.
Keywords: [2.2]paracyclophanes; planar chirality; benzophenone analogues; esters; primary amides